Epidemiological aspects of echinococcosis of the liver and other organs in the Republic of Uzbekistan - Azam Khasanovich Babadjanov (Elsevier, 2021)
Introduction: Recently, in international medical organizations, more and more interest is shown towards diseases in humans, among which the cystic form of echinococcosis (CE) is given special importance. As a zoonotic parasitic disease caused by the larval stage of cestodes belonging to the genus Echinococcus and the Taeniidae family, CE in 2014 was recognized globally by the UN Food and Agriculture Organization (FAO) and WHO as the second most important foodborne parasitic pathology. In the 2018, the European Food Safety Authority (EFSA) considered CE among the food-borne parasites of highest relevance in Europe. Purpose: to study the actual epidemiology of human echinococcosis lesion in the Republic of Uzbekistan for 2015–2019 to highlight the mean annual incidence of this pathology in all regions of the country, as well as the extensive value of the proportion of echinococcosis of the liver (EL), lungs (LE) and other localizations. Material and methods: The officially registered data for all regions of the country for 2015–2019 were studied. An ultrasound screening of the abdominal organs of the population of the Khorezm region was carried out during 2019 to determine the effectiveness of early diagnosis of EL. A total of 104,284 inhabitants were examined, of which 38,660 were children and 65,624 were adults. Results: According to the processed statistical data for all regions of the Republic of Uzbekistan for 2015–2019 on average, 2105.0 ± 43.3 patients with echinococcosis of various localizations were diagnosed. The mean annual incidence was 6.5 ± 0.09 per 100,000 inhabitants. The extensive value of the EL share was 79.4 ± 0.9% (1672.2 ± 35.6 on average per year), high-level rate - 5.2 ± 0.08 per 100,000 inhabitants; the proportion of LE was 14.0 ± 0.8% (295.2 ± 17.8), the prevalence was 0.9 ± 0.06 per 100,000 inhabitants; the proportion of echinococcosis of other localizations was 6.5 ± 0.5% (137.6 ± 13.4), the high-level value was 0.4 ± 0.03 per 100,000 inhabitants. The frequency of detection of the liver or other abdominal organs echinococcosis during screening ultrasound in the Khorezm region was 0.009%, in turn, the examination of family members of these patients increased this indicator to 0.011%.